Listen to Your Body The Wisdom of the Dao - Guo, Bisong; Powell, Andrew (University of Hawaii Press, 2001)
Listen to Your Body shows how you can promote health and natural well-being by modifying everyday actions to improve the flow of qi (the universal principle of energy). Breathing, eating, drinking, resting, washing, and many other small but vital actions--if carried out in the right way--can result in profound changes in body function. To give readers an understanding of the body's own natural medicine, the authors provide a clear explanation of the foundations of Traditional Chinese Medicine (TCM) with reference to qi and its flow through the body's meridians, the balance of yin and yang, and the body's energy centers. Readers will learn how to "tune in" to the signals the body transmits to warn of impending health problems; numerous case histories illustrate how this highly developed information system of the body works. Later chapters address the art of relaxation, bringing together the TCM approach to health with recent scientific studies. Finally the authors describe in detail how to apply the natural medicine of the body to daily life. They discuss illness prevention and provide specific guidance for the management of a range of health disorders. Exercises and simple routines are given, together with the basis for their therapeutic effect
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Jan 2018)
Keywords: Taoist hygiene